Consumo e Produção Sustentáveis - Dordio, Victor (Medi@ções, 2010)
The consequences of globalisation influence our daily lives and our environment. To face this complex situation and its impact on the planet, a word is being use to show the real challenge of globalisation: sustainability. This is mainly a dynamic process that affects all mankind and interferes with its development. Consumer citizenship and education for sustainable development will be particularly addressed as well as politics proposed and implemented by both the international bodies (UN, UNESCO, OECD,…) or the European Commission will be closely analysed.